Pemberdayaan UMKM desa pasuruhan melalui sertifikasi halal dan P-Irt - Azhar Mushufa; Habib Abdul Kholid A; Farhan Aly; Nadila Dwi Saputri; Putra Andrean (BEMAS: Jurnal Bermasyarakat, 2024)
The creative economy is a form of economy that relies on ideas and human resources, namely by utilizing one of the existing potentials and developing it using human creativity so that it can have economic value so that it can support the needs of everyday life. One example is MSMEs or community micro-medium enterprises or often called entrepreneurs where the business being run has a lower-medium economic level. Pasuruhan Village, one of which is a village in Mertoyudan sub-district, Magelang district, is a village with abundant potential for human resources and natural resources so that with the ideas and efforts of the community, this village has various industrial centers with medium levels, for example, snack businesses such as taro chips, cassava chips, Baked sponge, shallots and brown sugar (refined) industrial centers. With the existence of various food industries, this village can be said to be advanced in terms of the creativity of its people. However, there are several obstacles that exist in the businesses they run because their lack of understanding of the legality of a business is added to the complexity of making permits for their businesses making it difficult for their businesses to be marketed in a wider area. One of the obstacles is the difficulty of obtaining NIB permits. P-IRT licensing and Halal Certification for their products. Therefore, we, as students of UNIMMA, are moved to help them provide assistance for P-IRT licensing and Halal certification. The steps we use are: 1. Socialization of the importance of legality, 2. Collect data and collect the necessary files. 3. Conduct legal assistance by registering in the SPPIRT and SIHALAL systems. Our goal in carrying out this activity is as a form of our dedication to the Pasuruhan village community so that they obtain permits according to what they need. The result of this activity was that 50% of the total 24 businesses that applied for a business license or business legality obtained the business license they wanted so that it could support their economic activities in further marketing their products